Comparação dos dados antropométricos de pacientes em dois momentos de uma UTI pediátrica - Costa, Caroline Abud Drumond (Pontifícia Universidade Católica do Rio Grande do Sul, 2015)
Made available in DSpace on 2015-05-06T02:02:17Z (GMT). No. of bitstreams: 1 000467974-Texto+Parcial-0.pdf: 388194 bytes, checksum: d0ebb457bab4bbfa294aff23642e5442 (MD5) Previous issue date: 2015 === Introduction : The anthropometric nutritional assessment is a necessary way in children undergoing hospital. Despite of the malnutrition is significantly present in a hospital, it calls attention the nutritional transition that the country is going through, where the increase of overweight and obesity is increasing. Studies already show a fall of malnutrition even among patients in the Pediatric Intensive Care Unit. The objective of this study is to compare anthropometric data of patients in two moments of a Pediatric Intensive Care Unit. Methods : A retrospective cohort study, with patients in the Pediatric Intensive Care Unit of a university hospital in two periods of one year long, with four years interval. The data are from the unit's database. The nutritional assessment was performed based on the weight and height measured at the hospitalization moment. Parameters and classification of nutritional status were used recommended by the World Health Organization for the respective age groups. The Body Mass Index for Age was the chosen parameter to assess malnutrition and relate to severity and outcomes. Chi-square and Mann-Whitney test for comparison of patient data between the two moments were used. The differences were considered significant when p <0. 05.Results : The total sample of patients was 881 (406, current sample and 475, previous sample). There was a significant reduction by malnutrition in the current sample of patients (p = 0,03). In relation to outcomes, malnourished patients of the previous sample had a significant association with mortality and prolonged length of stay, while malnourished of the current study, did not show this association. Malnourished of the previous sample also showed significant association with severity on admission (Mensured by Pediatric Index Mortality 2), which was not observed in the current sample of malnourished ones. Conclusion : There was a significant reduction of malnutrition among patients of the same PICU when we compare two moments, suggesting that the nutritional transition is also present among pediatric critical patients. The current sample of malnourished also had better outcomes compared to the previous one. More studies are needed in order to confirm this nutritional transition and its impact among this group of patients. === Introdução : A avaliação nutricional antropométrica é uma ferramenta necessária em crianças submetidas à internação. Apesar da desnutrição estar presente de forma significativa em meio hospitalar, chama atenção a transição nutricional que o país que está passando, onde o aumento de sobrepeso e obesidade é crescente. Estudos já demonstram uma queda da desnutrição até mesmo entre pacientes internados em Unidades de Terapia Intensiva Pediátrica. O objetivo deste estudo é comparar dados antropométricos de pacientes em dois momentos de uma Unidade de Terapia Intensiva Pediátrica.Métodos : Estudo de coorte retrospectivo, com pacientes internados na Unidade de Terapia Intensiva Pediátrica de um hospital universitário em dois períodos de um ano com intervalo de 4 anos. Os dados são provenientes do banco de dados da unidade. A avaliação nutricional foi realizada a partir do peso e estatura aferidos no momento da internação. Foram utilizados parâmetros e classificação do estado nutricional recomendados pela Organização Mundial de Saúde, para as respectivas faixas etárias. O Indice de Massa Corporal para Idade foi o parâmetro escolhido para avaliar a desnutrição e relacionar com gravidade e desfechos. Foram utilizados os testes Qui-quadrado e Mann–Whitney para comparação dos dados dos pacientes entre os dois momentos. As diferenças foram consideradas significativas quando p<0,05.Resultados : A amostra total de pacientes foi de 881 (406 amostra atual e 475 amostra anterior). Houve redução significativa da desnutrição na amostra atual de pacientes (p=0,03). Em relação aos desfechos, os pacientes desnutridos da amostra anterior tiveram associação significativa com mortalidade e tempo de internação prolongado, enquanto que os desnutridos da amostra atual não apresentaram esta associação. Os desnutridos da amostra anterior também apresentavam associação significativa com gravidade na internação (Avaliado pelo Pediatric Index Mortality 2), o que não foi observado na amostra atual de desnutridos. Conclusão : Houve redução significativa da desnutrição entre os pacientes da mesma unidade de terapia intensiva pediátrica quando comparamos dois momentos, o que sugere que a transição nutricional está presente também entre pacientes pediátricos críticos. A amostra atual de desnutridos também teve melhores desfechos em relação à anterior. Mais estudos são necessários afim de confirmar essa transição nutricional e sua repercussão entre este grupo de pacientes.